2020
DOI: 10.3389/fmicb.2019.02912
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-Associated Methicillin-Resistant Staphylococcus aureus in Patients Admitted to Kuwait Hospitals in 2016–2017

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) has been reported to colonize and cause infections in animals as well as in humans. LA-MRSA isolates have only recently been identified in patients admitted to Kuwait hospitals. This study was conducted to characterize LA-MRSA isolates obtained from patients admitted to Kuwait hospitals. A total of 202 (7.1%) of 2,823 MRSA isolates obtained from clinical samples in 2016 and 2017 in 11 public Kuwait hospitals were assigned to lineages pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 64 publications
(85 reference statements)
0
19
1
Order By: Relevance
“…CC97 isolates belonged to either spa-type t1190 or t2802. spa-type t1190 is a rabbit-specific strain since it has been previously found in rabbit meat [36,37] and lesions [38]. As for spa-type t2802, it has been reported mostly associated with bovine livestock but also with humans [39,40].…”
Section: Characterization Of Cc97 Mrsa Isolatesmentioning
confidence: 99%
“…CC97 isolates belonged to either spa-type t1190 or t2802. spa-type t1190 is a rabbit-specific strain since it has been previously found in rabbit meat [36,37] and lesions [38]. As for spa-type t2802, it has been reported mostly associated with bovine livestock but also with humans [39,40].…”
Section: Characterization Of Cc97 Mrsa Isolatesmentioning
confidence: 99%
“…In addition, the presence of gene mecC has been reported for the first time in a Spanish river, highlighting the potential role of water in the dissemination of mecC MRSA [ 19 ]. S. aureus mecC was also isolated from animals and an urban wastewater treatment plant [ 55 ] and other studies highlighted the emergence of S. aureus mecC in livestock production, particularly in pigs in European countries [ 56 ]. In this sense, our two MRSA strains (negative for the mecA gene in the PBP2a test) were isolated from rivers (numbers 54 and 55 in Table 6 ) with high incidence from pig exploitations, which would reinforce this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CA-MRSA are usually more susceptible to non-beta-lactam antibiotics and carry SCC mec types IV, V, or VI ( David and Daum, 2010 ). The Livestock-associated MRSA (LA-MRSA) initially caused major problems in agriculture and were the leading cause of bovine mastitis ( Fluit, 2012 ) but have now become prominent among livestock, people associated with livestock and those with no previous contact with livestock ( Graveland et al, 2011 ; Köck et al, 2013 ; Wagenaar et al, 2009 ; Boswihi et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing tools including staphylococcal protein A (spa) typing, multilocus sequence typing (MLST), pulsed-field gel electrophoresis, staphylococcal cassette chromosome mec (SCC mec ) typing, DNA microarray, and whole genome sequencing (WGS) have been used in the epidemiologic surveillance of MRSA strains to detect and monitor emerging and reemerging infections as well as monitoring geographic spread and shifts of epidemic and endemic clones ( Pfaller, 1999 ; van Belkum et al, 2001 ; Monecke et al, 2011 ; Boswihi et al, 2016 , 2020a , 2020b ; Rebic et al, 2016 ). The application of these typing techniques to type MRSA from different geographic regions have shown that most of the MRSA infections reported worldwide were caused by a limited number of pandemic MRSA clones belonging to clonal complexes 5 (CC5), CC8/ST239, CC22, CC30, and CC45 ( Robinson and Enright, 2003 ; Monecke et al, 2011 ; Guthrie et al, 2020 ) although CA-MRSA isolates belong to more diverse genetic backgrounds compared to HA-MRSA ( Monecke et al, 2011 ; Udo, 2013 ; Tong et al, 2015 ; Guthrie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation